Solid oxide fuel cell (SOFC) performance evaluation, fault diagnosis and health control: A review - Peng, Jingxuan; Huang, Jian; Wu, Xiao-long; Xu, Yuan-wu; Chen, Haochun; Li, Xi (Journal of power sources, 2021)
Solid oxide fuel cells are a promising alternative energy source for new energy vehicles, distributed power generation and military equipment. It has the advantages of high efficiency, low noise, low emission and flexible fuel. In order to commercialize solid oxide fuel cells with high efficiency, long life and stable operation, the performance of the cells is usually improved by the following schemes: First, the performance of the system is evaluated, and the best possible static operating point and dynamic and static switching trajectories are obtained by assessing the operating characteristics as well as the dynamic and static characteristics of the system. Secondly, fault diagnosis of the system is used to detect possible faults in the system in time and prevent the damage of faults to the system performance. Finally, the corresponding control strategy is formulated for the operating characteristics of the SOFC and the possible faults to ensure the efficient and stable operation of the system. This paper presents the current status of research on performance evaluation, fault diagnosis, and health control of solid oxide fuel cell systems, and presents current research gaps as well as future directions. •The current research gaps and future directions of SOFC are presented.•Performance evaluation: modeling, experimental analysis, performance prediction.•Fault diagnosis: stack and system diagnosis, simultaneous multi-fault diagnosis.•Health control: stack control, system control, fault tolerance control.